2008
DOI: 10.1152/ajpregu.00115.2008
|View full text |Cite
|
Sign up to set email alerts
|

Central pathway for spontaneous and prostaglandin E2-evoked cutaneous vasoconstriction

Abstract: Rathner JA, Madden CJ, Morrison SF. Central pathway for spontaneous and prostaglandin E2-evoked cutaneous vasoconstriction. Am J Physiol Regul Integr Comp Physiol 295: R343-R354, 2008. First published May 7, 2008 doi:10.1152/ajpregu.00115.2008.-A reduction of heat loss to the environment through increased cutaneous vasoconstrictor (CVC) sympathetic outflow contributes to elevated body temperature during fever. We determined the role of neurons in the dorsomedial hypothalamus (DMH) in increases in CVC sympathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 72 publications
8
118
0
Order By: Relevance
“…The absence of evidence for brain sites intermediate between the POA and the rostral medullary raphe that are required for the POA efferent signaling for temperature-dependent CVC control supports the significance of the direct projection from POA neurons to the rostral medullary raphe as the efferent pathway for febrile and thermoregulatory control of cutaneous vasoconstriction (30,33,34). The present results do not exclude the possibility that warm-responsive LPBd neurons have axonal branches that could bypass the POA and provide thermosensory signals directly to sites, such as the rostral medullary raphe, in the efferent pathways controlling thermoregulatory effectors, but this possibility seems unlikely, because there are very few projections from the LPB to the rostral medullary raphe (14), and antagonizing glutamate receptors in the MnPO resulted in a nearly complete blockade of heat-defensive responses to skin warming or stimulation of LPBd neurons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The absence of evidence for brain sites intermediate between the POA and the rostral medullary raphe that are required for the POA efferent signaling for temperature-dependent CVC control supports the significance of the direct projection from POA neurons to the rostral medullary raphe as the efferent pathway for febrile and thermoregulatory control of cutaneous vasoconstriction (30,33,34). The present results do not exclude the possibility that warm-responsive LPBd neurons have axonal branches that could bypass the POA and provide thermosensory signals directly to sites, such as the rostral medullary raphe, in the efferent pathways controlling thermoregulatory effectors, but this possibility seems unlikely, because there are very few projections from the LPB to the rostral medullary raphe (14), and antagonizing glutamate receptors in the MnPO resulted in a nearly complete blockade of heat-defensive responses to skin warming or stimulation of LPBd neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Recent findings on the efferent control of sympathetic CVC tone indicate that the effector signaling from the POA leading to temperature-dependent CVC control is mediated by the rostral medullary raphe including the rostral raphe pallidus (30), a site of sympathetic premotor neurons controlling skin blood vessels (31,32). The absence of evidence for brain sites intermediate between the POA and the rostral medullary raphe that are required for the POA efferent signaling for temperature-dependent CVC control supports the significance of the direct projection from POA neurons to the rostral medullary raphe as the efferent pathway for febrile and thermoregulatory control of cutaneous vasoconstriction (30,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The rat's tail is a major organ of heat loss, and its circulation is regulated by sympathetic vasoconstrictor nerves under the control of the brain. Sympathetic premotor neurons controlling the tail circulation are located in the rostral medullary raphé (Smith et al, 1998;Tanaka et al, 2002Tanaka et al, , 2007Nakamura et al, 2004;Ootsuka et al, 2004;Ootsuka and Blessing, 2005;Ootsuka and McAllen, 2005) and to a lesser extent the rostral ventrolateral medulla (Tanaka et al, 2002;Ootsuka and McAllen, 2005;Rathner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Under warm conditions, brain transection caudal to the preoptic area (Rathner et al, 2008) or neuronal inhibition in the preoptic area (Osborne and Kurosawa, 1994) induce tail vasoconstriction, indicating that the tail vasomotor supply is under tonic inhibitory regulation by preoptic neurons. We recently showed that neurons in two distinct preoptic loci contribute to this tonic inhibition; a rostromedial preoptic region (RMPO) surrounding the organum vasculosum of the lamina terminalis and the median preoptic nucleus (MnPO), and a preoptic region centered ϳ1 mm caudolaterally (CLPO) (Tanaka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that warm-sensitive neurons in PO/AH send excitatory signals to vasodilator neurons and inhibitory signals to vasoconstrictor neurons. PO/AH neurons controlling cutaneous blood flow project to the rostral medullary raphe region directly [26], suggesting that distinct populations of PO/AH neurons control thermogenesis and cutaneous vasomotion. This concept is supported by the observation that the two thermoregulatory mechanisms are activated at different threshold temperatures [27].…”
Section: Thermoregulatory Neuronal Network Comprising Po/ah Thermosementioning
confidence: 99%